2011
DOI: 10.1016/s1001-0742(10)60503-7
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi alter the response of growth and nutrient uptake of snap bean (Phaseolus vulgaris L.) to O3

Abstract: The effects of arbuscular mycorrhizal fungi (AMF) Glomus mosseae on the responses to elevated O 3 in growth and nutrition of snap bean (Phaseolus vulgaris L. cv Guangzhouyuan) were investigated. Exposure was conducted in growth chambers by using three O 3 concentrations (20 (CF), 80 (CFO1) and 120 nL/L (CFO2); 8 hr/day for 75 days). Results showed that elevated O 3 slightly impacted overall mycorrhizal colonization, but significantly decreased the proportional frequency of hypha and increased the proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…Thus, actual comparisons between the 2 experiments are difficult to make. Present results also conflict with our previous report, in which the same plant species (Phaseolus vulgaris L. 'Guangzhouyuan') was used to investigate the effect of elevated O 3 on mycorrhizal colonization (Wang et al 2011). Results showed that overall mycorrhizal colonization was slightly decreased by 80 and 120 nL/L O 3 , but the proportional frequency of hypha significantly decreased and the proportional frequency of spores and vesicles significantly increased with elevated O 3 .…”
Section: O 3 Effects On Mycorrhizal Colonization Ratecontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, actual comparisons between the 2 experiments are difficult to make. Present results also conflict with our previous report, in which the same plant species (Phaseolus vulgaris L. 'Guangzhouyuan') was used to investigate the effect of elevated O 3 on mycorrhizal colonization (Wang et al 2011). Results showed that overall mycorrhizal colonization was slightly decreased by 80 and 120 nL/L O 3 , but the proportional frequency of hypha significantly decreased and the proportional frequency of spores and vesicles significantly increased with elevated O 3 .…”
Section: O 3 Effects On Mycorrhizal Colonization Ratecontrasting
confidence: 99%
“…BGCBJ07), purchased from Beijing Academy of Agricultural and Forestry Sciences (Beijing, China), was propagated by the host plant of broomcorn (Sorghum vulgare). Glomus aggregatum was proved to have a good symbiotic relationship with snap bean (Phaseolus vulgaris L.) in a previous experiment (Wang et al 2011). AM inoculum was a mixture of spores, mycelium, sandy soil, and root fragments.…”
Section: Am Fungi and Soilmentioning
confidence: 98%
See 2 more Smart Citations
“…However, recently, the approach of soil microbial inoculation to ameliorate salinity stress in plants [19] has gained more attention. Microbial inoculants, such as arbuscular mycorrhizal fungi (AMF) and Rhizobium, have been previously studied as they are ubiquitous in soil and provide a low-cost natural means of improving nutrient acquisition in stressed soil under adverse environmental conditions [20][21][22][23]. Specifically, soil inoculation with AMF and Rhizobium can potentially reduce environmental pollution by lowering the application of synthetic fertilizers in the soil [24,25].…”
Section: Introductionmentioning
confidence: 99%